Penerapan Praktik Sholat Fardhu Setiap Hari Jum’at Untuk Menanamkan Nilai Agama Pada Anak Usia Dini di Raudlatul Athfal Al Ma’ruf Jember - Jauhari; Siti Julaikha (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Prayer practice needs to be taught from an early age so that it becomes a habit ingrained in children and difficult to abandon. The purpose of this research is to describe the implementation of daily Friday prayer practice to instill religious values in early childhood at Raudlatul Athfal Al Ma'ruf Jember. The research method used is qualitative research with a case study approach. The research location is Raudlatul Athfal Al Ma'ruf Ajung, Jember Regency. The informants are the head, teachers, and students of Raudlatul Athfal Al Ma'ruf. Data collection techniques include observation, interviews, and documentation. Data analysis involves data reduction, data presentation, and data verification. Data validity is ensured through the triangulation of techniques and sources. The research findings show that the activities are planned, implemented, and evaluated. Planning takes place one day before the practice. The implementation begins with the recitation of the 99 Names of Allah, short surahs, names of angels, and hadiths. It is then followed by practicing ablution, the call to prayer and the call to stand, and the practice of obligatory prayers. Evaluation is done by assessing the level of discipline in worship